Gambaran Pelaksanaan Manajemen Strategi Terhadap Kinerja Pada PT Wisang Utama Mandiri - Ghora Wisnu Samudra; Moh. Rifaizal Lahmudin; Siti Mujanah (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2023)
This study aims to investigate the impact of implementing strategic management on the performance of PT Wisan Utama Mandiri. In the power industry, PT Wisang Utama Mandiri plays an important role in providing high-quality services and meeting customer needs. However, intense competition and dynamic changes in the business environment demand the adoption of effective strategies. This research uses a qualitative approach with a case study method at PT Wisang Utama Mandiri. Data was collected through in-depth interviews with company management, analysis of internal documents, and direct observation of operational activities. The results of this study show that the implementation of effective strategic management has a positive impact on the performance of PT Wisang Utama Mandiri. With a clear and directed strategy, the company is able to optimize the use of its resources, increase competitive advantage, and strengthen relationships with customers. In addition, strategic management also helps companies in identifying and managing risks associated with business operations.